2007
DOI: 10.1002/jbm.a.31542
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass‐induced osteoblast differentiation: A noninvasive spectroscopic study

Abstract: Here, we report on a rapid, noninvasive biophotonics system using Raman spectroscopy to detect real-time biochemical changes in foetal osteoblasts (FOBs) following exposure to 45S5 Bioglass (BG)-conditioned media. Bio-Raman spectroscopy, combined with multivariate statistical analysis techniques (principal component analysis and least squares analysis), was able to noninvasively identify biochemical differences in FOBs cultured for different time periods and between FOBs exposed/or not to BG-conditioned media.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 62 publications
0
65
0
2
Order By: Relevance
“…The bio-Raman system offers the potential of monitoring and maintaining cell phenotype by in situ spectroscopic analysis of the cells Jones et al 2005;Jell et al 2008;Swain et al 2008a;Gentleman et al 2009). Notingher et al show that two statistical-based spectroscopic data management programs, called principal component analysis and linear discriminant analysis (LDA), are powerful tools for distinguishing cell phenotypes in real time.…”
Section: Bio-raman Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bio-Raman system offers the potential of monitoring and maintaining cell phenotype by in situ spectroscopic analysis of the cells Jones et al 2005;Jell et al 2008;Swain et al 2008a;Gentleman et al 2009). Notingher et al show that two statistical-based spectroscopic data management programs, called principal component analysis and linear discriminant analysis (LDA), are powerful tools for distinguishing cell phenotypes in real time.…”
Section: Bio-raman Test Methodsmentioning
confidence: 99%
“…Notingher et al show that two statistical-based spectroscopic data management programs, called principal component analysis and linear discriminant analysis (LDA), are powerful tools for distinguishing cell phenotypes in real time. Bio-Raman spectroscopic analyses were made of MG63 immortal human osteosarcoma-derived osteoblasts and compared with primary human osteoblasts, obtained from surgically excised femoral heads ( Jell et al 2008). An LDA model prepared from the data showed high cross-validation sensitivity (100%) and high specificity (95%) for discriminating the MG63 cells from the primary cells, with 96 per cent of the cells being correctly classified either as tumour-derived or non-tumourderived cells.…”
Section: Bio-raman Test Methodsmentioning
confidence: 99%
“…Cells adhere to the growth substrate by means of FAs, which, upon maturation, are characterised by the presence of vinculin (Burridge and ChrzanowskaWodnicka, 1996). Surfaces that induce the formation of prominent FAs support osteogenic differentiation of stem and progenitor cells, whereas small and evenly spread FAs are linked to a decrease in osteogenic and an increase in adipogenic commitment (Abagnale et al, 2015;Biggs et al, 2009;Kilian et al, 2010). In contrast to these studies, conducted with various surface topographies and micropatterns created in polystyrene and polyimide, the results presented here indicated that the mature FAs of hASCs on S53P4 and 1-06 were small and evenly dispersed despite the evident osteogenic potential of both BaG types.…”
Section: Ojansivu Et Al Mechanisms Of Bioglass Induced Osteogenic mentioning
confidence: 99%
“…Key mechanisms leading to enhanced new bone growth are now known to be related to the controlled release of ionic dissolution products from the degrading bioactive glass, especially critical concentrations of biologically active, soluble silica and calcium ions [8,191]. Recent studies have shown that bioactive (partially) resorbable glasses and their ionic dissolution products enhance osteogenesis by regulating osteoblast proliferation, differentiation, and gene expression [7,41,51,[191][192][193][194][195][196][197][198].…”
Section: Ion Dissolution From Bioactive Glasses: Genetic Control Of Omentioning
confidence: 99%